2018
DOI: 10.1371/journal.pone.0203612
|View full text |Cite
|
Sign up to set email alerts
|

Copper-caused oxidative stress triggers the activation of antioxidant enzymes via ZmMPK3 in maize leaves

Abstract: Copper (Cu) is a necessary trace element participated in many physiological processes in plants. But excessive Cu2+ is toxic, which can activate intracellular signals that lead to cellular damage. The mitogen-activated protein kinase (MAPK) cascade is at the center of cell signal transduction and has been reported to be involved in stress-related signaling pathways. ZmMPK3, a kind of MAPKs in maize cells, can be activated by diverse abiotic stresses. In the present study, we investigated the effects of Cu2+ on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 38 publications
4
60
0
Order By: Relevance
“…In this study, increasing Cu concentration in culture medium led to the increase in H 2 O 2 and MDA in the leaves of cotton seedling Fig.3A . The results were in harmony with ndings of previous studies in maize leaves (Liu et al, 2018) and in Medicago sativa seedling shoot [17] In this current study, Cu induced H 2 O 2 incited directly lipid membrane damage in cotton leaves. High concentration of ROS caused enzyme inactivation, lipid peroxidation, and oxidation of nucleic acids [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, increasing Cu concentration in culture medium led to the increase in H 2 O 2 and MDA in the leaves of cotton seedling Fig.3A . The results were in harmony with ndings of previous studies in maize leaves (Liu et al, 2018) and in Medicago sativa seedling shoot [17] In this current study, Cu induced H 2 O 2 incited directly lipid membrane damage in cotton leaves. High concentration of ROS caused enzyme inactivation, lipid peroxidation, and oxidation of nucleic acids [18].…”
Section: Discussionsupporting
confidence: 92%
“…The accumulation of H 2 O 2 in leaves was measured by monitoring the A415 of the titanium-peroxide complex following the method described by Liu et al [28]. Absorbance values were calibrated to a standard curve generated with known concentrations of H 2 O 2 .…”
Section: Detection Of H 2 O 2 and Mda Levelmentioning
confidence: 99%
“…However, previously we reported that jute could tolerate the Cu level up to 300 mg kg −1 and Cu contents more than 300 mg kg −1 in the soil caused decreased in plant growth [46]. This might be due to the high level of Cu accumulated in the cells, which affects the plant growth and development [7,17]. Another reason behind this mechanism is also due to the reduction in essential elements in the soil and an increased in Cu contents in plant cells, causing chlorotic symptoms [47].…”
Section: Effect Of Cu On Plant Morphology and Compositionmentioning
confidence: 94%
“…Furthermore, normal concentration of Cu is nontoxic to plants, whereas Cu toxicity directly disturbs the structure of chloroplast, mitochondrial apparatus, nucleus, and other cellular organelles [6,7,13,14]. Excess Cu causes damage to the cellular membrane organelles by increasing ROS in plant cells and tissues, causing peroxidation of substances on the cell surface [11,[15][16][17]. ROS, which are toxic and remove by the activities of antioxidant compounds [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Under salinity stress, the exogenous supplementation of Se to maize (Zea maize L.) plants resulted in the upregulation of expression of mitogen activated protein kinase (MAPK5 and MAPK7) and calcium-dependent protein kinase (CPK11) genes and stimulated the antioxidant defense system under salt stress [29,163]. It has been reported that MAPK flow is at the center of cell signal transduction and implicated in stress-related signal pathways [164]. Abscisic acid (ABA) accumulation could be stimulated under salinity stress [165], which in turn produces H 2 O 2 , causing the activation of MAPK, resulting in stimulated expression and activities of antioxidant enzymes [166].…”
Section: Se-mediated Improvement In the Upregulation Of Enzymatic Andmentioning
confidence: 99%